2001
DOI: 10.1177/172460080101600108
|View full text |Cite
|
Sign up to set email alerts
|

Histological Grade in Breast Cancer: Association with Clinical and Biological Features in a Series of 229 Patients

Abstract: In order to study the association of histological grade (HG) with specific clinical and biological parameters which may influence the clinical behavior of infiltrating ductal carcinomas of the breast (IDC), we analyzed in 229 tissue samples the cytosolic concentrations of estrogen receptor (ER), progesterone receptor (PR), pS2, cathepsin D, hyaluronic acid (HA) and tissue-type plasminogen activator (t-PA), as well as those of the erbB2 oncoprotein, epidermal growth factor receptor (EGFR), HA, CD44v5 and CD44v6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 32 publications
1
3
0
2
Order By: Relevance
“…A significant association between breast cancer grade and tumor size has also been described by Ruibal et al. ( 11 ), who found that a larger size was correlated with a higher histological grade. In the present study, the mean tumor size ± SD was 4.48 ± 1.73 cm, which did not correlate with any DCE-MRI perfusion parameters ( p > 0.05).…”
Section: Discussionsupporting
confidence: 67%
“…A significant association between breast cancer grade and tumor size has also been described by Ruibal et al. ( 11 ), who found that a larger size was correlated with a higher histological grade. In the present study, the mean tumor size ± SD was 4.48 ± 1.73 cm, which did not correlate with any DCE-MRI perfusion parameters ( p > 0.05).…”
Section: Discussionsupporting
confidence: 67%
“…They were less likely be lymph node positive, have a lobular phenotype and be treated with chemotherapy. Studies by Ruibal et al and Thike et al showed an association of the histological tumor grade with the ER/PR content 11,13 . A transition from lower to higher histological grades was accomplished by a decrease in ER/PR content.…”
Section: Table I : Patient Profile Of Cancermentioning
confidence: 95%
“…Only about one half of patients with early breast cancer are treated and cured by local surgical excision alone. Therefore, it is important to identify the set of patients in whom the disease is destined to recur and which patients are likely to benefit from systemic chemotherapy 10,11 .…”
Section: Methodsmentioning
confidence: 99%
“…También hemos considerado el tamaño, afectación ganglionar axilar (N), las metástasis a distancia (M), la ploidía, índice de DNA (IDNA) y la fase de sín-tesis celular (FS), medidas por citometría de flujo en muestras en fresco. El tratamiento de las muestras y los detalles técnicos han sido expuestos en otro trabajo 4 . El estudio estadístico fue realizado mediante el programa BMPD3 y, dado que los resultados obtenidos seguían una distribución no paramétrica, hemos utilizado el test de Mann Whitney, así como el del chi cuadrado para la comparación de proporciones.…”
Section: Sr Directorunclassified